EFEKTIVITAS RESTRUKTURISASI PEMBIAYAAN DI MASA PANDEMI COVID-19 TERHADAP PENURUNAN NPF DI BANK SYARIAH INDONESIA - Karina Utami (2022)
The biggest income of a bank is in financing transaction activities. During the Covid-19 pandemic, banks experienced an increase in the level of non-performing financing due to the implementation of restrictions on community activities. To anticipate the emergence of large losses in banks, the Otoritas Jasa Keuangan as the regulator in collaboration with Bank Indonesia made a restructuring policy to save banks and ease the burden on the public who will pay their obligations to banks. This study was conducted to determine the effectiveness of financing restructuring to decrease NPF in Indonesian Islamic Banks. The methodology used is a descriptive qualitative method with a case study approach. The results of this study prove that the financing restructuring carried out by Bank BSI has been effective in reducing the NPF ratio, this is evidenced by the declining NPF ratio data compared to before the implementation of the financing restructuring, other effective indicators are also met, seen from the indicators of achieving goals where Bank BSI has reduced the NPF ratio. and assisting customers in accordance with the objectives of implementing financing restructuring, adaptation indicators where Bank BSI has carried out socialization related to the implementation of financing restructuring, and integration indicators where Bank BSI has provided restructuring in accordance with the right targets. Keywords: Covid-19, Financing Restructuring, NPF